Comparativ Analys of Modern Concepts of Controlling - Гринюк, О. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Controlling concepts systematization is implemented in two directions (according to controlling functional role (task) in control system loop; according to controlling goals) based on conducted comparative analysis of modern controlling concepts. Within each direction concepts grouping is carried out on partial signs. Features of each of the provided controlling concepts are considered. The main concepts, which will be the basis for further research concerning formation of risk controlling system at oil and gas enterprises, are defined.